COMPARATIVE ANALYSIS ON DIVERSITY PATTERN OF PINEAPPLE BASED ON PHENOTYPIC AND RAPD MARKERS - Sobir Sobir; Siska Indriajaya Apriyani; Hajrial Aswidinnoor; Yuniarti Yuniarti (Floribunda, 2006)
Sobir, Siska Indriajaya Apriyani, Hajrial Aswidinnoor & Yuniarti. 2006. Comparative Analysis on Diversity Pattern of Pineapple Based on Phenotypic And RAPD Markers. Floribunda 3(2): 44-51. – Pineapple is mostly propagated through vegetative mean, and tend to have narrow genetic variability; therefore, powerful method is required to differentiate their genetic variability, and consequently 20 Ananas commosus  accessions from nine locations inIndonesia and two accessions fromIvory Coast, were subjected to genetic variability analysis. This reseach utilizes their phenotypic performance and RAPD markers to evaluate the genetic distance and relationship among those accessions. Twenty-seven morphological characters and 29 RAPD bands had been utilized in this study. Cluster analysis revealed that based on morphological markers the accessions were separated accessions from 0.36 to 0.84 of similarity coefficient, and three primary groups could be distinguished at similarity coefficient of 0.35. Subsequently RAPD analysis has been separated the accessions at 0.62-1.00 of coefficient of similarity. From this analysis, three primary groups constructed at 0.67, and it is able to differentiate Queen and Smooth Cayenne type accessions. The concurrence analysis on morphological and RAPD analysis, showed the very weak Rohlf correlation value (r=0.0747), which indicated that grouping of pineapple accessions should be combination of morphological characters and RAPD analysis. Combination morphological showed that accessions distributed from 0.49 to 0.81 of similarity coefficient level, and at 0.56 level similarities, the pineapple accessions were clustered into four primary groups and it is able to differentiate Queen and Smooth Cayenne type accessions.